Orientalism: Edward Said's Postcolonial Thoughts and Theories Against the Eastern World and Islam - Yunika Sari; Pujawati Pujawati; Miftahul Ulum Bahtiar (UIN Sunan Gunung Djati Bandung, 2023)
Orientalism is a form of colonialism carried out by Western oriental intellectuals, with the mission to dominate the Eastern world, especially Islam. However, not all oriental people are subjective with a negative view of the East and Islam, but there are also groups of oriental people who are objective and have a positive influence on the Eastern world and Islam. One of them is Edward W. Said, an American Palestinian intellectual. Edward was the first person to bring up the name orientalism in his work. In his work, Edward describes orientalism and postcolonial theory. The work also succeeded in dismantling the perspectives of Western orientalists who tried to hegemony and dominate the East and Islam in the realm of science. This is what researchers feel is necessary to understand how an orientalist figure made a big contribution to help the East world fight against Western world colonialism. This research is based on a qualitative descriptive method, accompanied by a literature review method, with the main source being Edward's books. This study discusses the thoughts of Edward W. Said, postcolonial theory and his criticisms. The purpose of studying Edward's thought is to know and describe ideas and understand Edward's thoughts on orientalism, then to understand Edward's views on postcolonial theory and his criticisms. In conclusion, with the existence of orientalism and Edward W. Said's postcolonial theory, it can provide an opportunity for the world community to voice justice for the occurrence of Western colonialism which in fact is still a social fact for Western atrocities in Eastern countries, especially Islam.